2022
DOI: 10.1136/bmjopen-2021-056598
|View full text |Cite
|
Sign up to set email alerts
|

Record linkage studies of drug-related deaths among former adult prisoners who have been released to the community: a scoping review protocol

Abstract: IntroductionPrisoners often have a complex mix of health and care needs including needs relating to mental and physical ill-health conditions. In addition, substance use disorders are common in prisoners. The transition between prison and community poses risks in terms of a disruption to treatment and care and a deterioration in health. Studies have demonstrated an increased risk of drug-related deaths among former prisoners during the first weeks following release from custody. The aim of this scoping review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This broader scope was informed largely by the results of previous systematic reviews/meta-analysis regarding reported high levels of heterogeneity [5][6][7]. The methods used to conduct this scoping review have been published previously as a protocol [9] and a summary of the methodology is provided here. This review followed the first five stages of the framework for conducting scoping reviews by Arksey and O'Malley [10] and adhered to the guidance developed by the Joanna Briggs Institute (JBI) and the JBI Collaboration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This broader scope was informed largely by the results of previous systematic reviews/meta-analysis regarding reported high levels of heterogeneity [5][6][7]. The methods used to conduct this scoping review have been published previously as a protocol [9] and a summary of the methodology is provided here. This review followed the first five stages of the framework for conducting scoping reviews by Arksey and O'Malley [10] and adhered to the guidance developed by the Joanna Briggs Institute (JBI) and the JBI Collaboration.…”
Section: Methodsmentioning
confidence: 99%
“…The full list is found in appendices 1, 2, 3, and 4. The search strategy for MEDLINE was developed by JAC and MD with assistance from the Subject Librarian for the School of Medicine, Dentistry and Biomedical Sciences in Queen's University Belfast, and was published with the review protocol [9]. JAC and MD developed search strategies for EMBASE, PsychINFO and Web of Science, and all search strategies used in this review have been provided as supplementary material (appendices 1, 2, 3, and 4).…”
Section: Stage 2: Identifying Relevant Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes the cohort population younger and healthier than the Canadian population. Substance use harm events occurring in correctional settings and following release are well documented and particularly prevalent immediately following release, [36][37][38][39][40][41][42][43][44][45] when many individuals are without an address or are residing in a group home so are not likely to be included with CanCHEC data. A recent scoping review also suggests that prescription misuse is a growing concern among older adults in Canada, 46 suggesting that harm events in nursing homes may also be missed in the CanCHEC data.…”
Section: Strengths and Limitations Of Canchecs In Constructing Substa...mentioning
confidence: 99%